Les relations ville-port à Rio de Janeiro : entre difficultés et perspectives de développement - Bertrand Cozic (Confins, 2012)
The productive reorganization in progress since the early 70s projects each time a little more cities and ports as such mains actors of the territory integration in the globalization’s flows. In Rio de Janeiro, since the end of the 90s, we can observe numerous modernisation initiatives of the port system, and of the city waterfront revitalization. The port is actually really dynamic in national level for the containers traffic, vehicles (Roll-on/Roll-Off), Oil and Oil products (Petrobras Logistic port support) and in Tourism with the passengers transport. However, Rio de Janeiro Port-city relationships are characterized by serious difficulties. Until today, Port Authorities, the city, private actors and civil society have not formulated a real concerted development project including the City and the Port. Rio de Janeiro Port-city relationships are influenced by old Industrial Era practices of the country, presenting both entities such as incompatibles. In one side, the city is interested in old port spaces revitalization, by developing huge tourism urban project based on several international experiences; on the other side, the port is interested in developing his activities in order to attend Globalization growth flows. However, true innovating development policies are experimented, such as port cities in the Northern Range or in Spain, places where we can observe a united development of the two dynamics through the elaboration of concerted strategies.